Initial Research of Renewable Energy Resources for Hybrid Microgrid Implementation, Using Solar and Wind; Transforming the Diesel Dependence. Case Study of Mamburit Island - Indonesia - Eric Marcos Hughes Arrocha; Dedet Candra Riawan; Rony Seto Wibowo (Department of Electrical Engineering ITS and FORTEI, 2022)
Electrical demands are growing rapidly in the world, especially in larger cities, and Indonesia is not an exception. Indonesia's average peak demand is projected to increase by 73% (reaching 43.7 GW) in 2020, by 142% (reaching 61.2 GW) in 2025, and by 205% (reaching 77.3 GW) in 2030, compared with 25.3 GW in 2010 [1]. However, the challenge of completing the growing demand in big cities reveals another huge problem, which are those small villages, communities and islands who doesn’t have access to electricity until now.Many countries apply and use the concept of Micro Grid [MG] as an effective solution, which can be defined as: the grid where each generator or load has to take part in the network management, joining in reactive power supply/voltage control, active power supply/frequency control, fault ride-through capability, and power quality control independently [5].Using an Indonesian remote Island as a real case, different renewable energy sources available will be evaluated to propose the best Micro Grid design integration system to supply electricity facility.This research will describe the principles, measurement process and general mathematical description for the application of the MG model integration.Planning to minimize the traditional electric sources of fossil dependence, the design for Mamburit Island in Sumenep-Indonesia will integrate different generation sources such as, Solar Panel System [PV/SHS] showing Daily Average Irradiation [DNI] of 5.78 kwh/ , vertical Axis Wind Turbine [VAWT] shows wind speed annual average of 8.82 m/s and energy Storage system [ESS] as a real, feasible and friendly options to complete the demand, integrated with Engine Diesel Generator [EDG] present as the actual main sources; minimizing the fossil dependence, through MG principle. Keywords— Smart Micro Grid, Micro Grid Integration, Renewable Energy.